2015
DOI: 10.1016/j.tox.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Key role of phosphodiesterase 4A (PDE4A) in autophagy triggered by yessotoxin

Abstract: Understanding the mechanism of action of the yessotoxin (YTX) is crucial since this drug has potential pharmacological effects in allergic processes, tumor proliferation and neurodegenerative diseases. It has been described that YTX activates apoptosis after 24h of treatment, while after 48 h of incubation with the toxin a decrease in cell viability corresponding to cellular differentiation or non-apoptotic cell death was observed. In this paper, these processes were extensively studied by using the erythroleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…In this regard, the K-562 cell line did show a decrease in cell proliferation accompanied by an increase in LDH release after both 24 and 48 h of YTX incubation. That is, after YTX treatment the number of K-562 cells was decreasing because cell death was triggered, since apoptosis and autophagy activation was observed, the same as it was described in previous studies (Fernandez-Araujo et al, 2014; Fernández-Araujo et al, 2015). However, in the lymphoblastoid cell line, no effect in cell viability was observed in the first 24 h of treatment, and after 48 h, cell proliferation was decreased without any LDH release, that is without cellular lysis.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In this regard, the K-562 cell line did show a decrease in cell proliferation accompanied by an increase in LDH release after both 24 and 48 h of YTX incubation. That is, after YTX treatment the number of K-562 cells was decreasing because cell death was triggered, since apoptosis and autophagy activation was observed, the same as it was described in previous studies (Fernandez-Araujo et al, 2014; Fernández-Araujo et al, 2015). However, in the lymphoblastoid cell line, no effect in cell viability was observed in the first 24 h of treatment, and after 48 h, cell proliferation was decreased without any LDH release, that is without cellular lysis.…”
Section: Discussionsupporting
confidence: 75%
“…Either, the activation of both intrinsic and extrinsic apoptosis processes through PDE4A modulation in K-562 cells after 24 h YTX incubation, as well as the autophagy cell death triggered through the PDE4A modulation in the same cell line after 48 h of YTX treatment were extensively studied (Fernandez-Araujo et al, 2014; Fernández-Araujo et al, 2015). Therefore, the activation of these pathways was checked in the lymphoblastoid cell line.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies also claimed in vitro toxicity [25,26]. The mechanism of action is unknown, but YTX has been shown to interfere with the autophagy pathway [27]. Although the group of azaspiracids displays symptoms similar to DSP [28], in vivo studies in mice showed more severe effects than OA toxins [29].…”
Section: Introductionmentioning
confidence: 99%